ANALISIS DAMPAK PERUBAHAN SOSIAL DENGAN KEBERADAAN PT. CITRA MAHKOTADI DESA BATAS NANGKA KABUPATEN MELAWI - Maria Magdalena Rika; Rustiyarso Rustiyarso; Izhar Salim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis thesis was entitled Analysis the Impact of Social Change with the Existence of PT. Citra Mahkota in the Nangka Batas Village Melawi Regency. The research method used was descriptive method with a form of qualitative research. Data collection was done by observation, interviews and documentation. Data sources used was primary and secondary data sources. The data obtained comes from documentation, observation and interviews. The results of this research proved that: There were positive and negative impacts of planned social changes in the past and present with the existence of PT. Citra Mahkota. The positive impact was previously in the Batas Nangka village, there was no connecting road to the village around and now there was a connecting road to the surrounding village. What used to be a very minimal community economy but at present the community's economy has increased. What used to be the working community as a shifting farmer was now switching they work in oil palm plantations, which had a negative effect because the work system of the community was more individual. The negative impact of unplanned social change was that the presence of oil palm plantations in the Batas Nangka village often suffers from drought due to oil palm trees that absorb a lot of water. Keywords: Analysis, Impacts of Social Change, PT. Citra Mahkota